A Review Study on Trust and Breach of Psychological Contract - Saravana Kumar, Karuppannan (2011)
The aim of this study is to review on trust and breach of psychological contract. The purpose of the study is to identify briefly on the psychological contract and the important of psychological contract to the employer as well as employees. It is also to learn the content of psychological contract and to study in brief on the types of psychological contract, breach and violation. This study is carried out to identify the reactions to breach and violation of psychological contract, list down the reasons for a lack of trust among the employees and to learn the ways how the employers gain and maintain the trust. The consequences to the organizations when the employee’s trust are lacking and what will happen if employees trust is high also has studied to add knowledge on psychological contract aspects. Lastly, the impact to the employees when the psychological contract is violated also has been reviewed. For this research, qualitative research method was used to gather the data. The data obtained from journals, case studies and books and magazines was reviewed to gather the information for this project. The review found that there were four main importances. First it explained in detail the meaning the meaning of psychological contract and its importance to both employers and employees. Secondly, the research has explained briefly on types of psychological contract, types of breach and violation of psychological contract. Thirdly, the research has indicate the trust; from the perspective of employees and employers. Fourthly, the research explains the impacts for violation of psychological contract. From the review it could be concluded that breach of psychological contract can be upgraded if both parties; employees and employers are working together in a line. They have to change because of economical, political and social changes, therefore the working relationship also changing. To improve the employees from breach of psychological contract, the organizations can implement some of the suggested methods to reduce the breach of psychological contract.